2015
DOI: 10.1002/cbf.3100
|View full text |Cite
|
Sign up to set email alerts
|

A review on protein–protein interaction network of APE1/Ref‐1 and its associated biological functions

Abstract: Apurinic/apyrimidinic endonuclease 1 (APE1) is a classic example of functionally variable protein. Besides its well-known role in (i) DNA repair of oxidative base damage, APE1 also plays a critical role in (ii) redox regulation of transcription factors controlling gene expression for cell survival pathways, for which it is also known as redox effector factor 1 (Ref-1), and recent evidences advocates for (iii) coordinated control of other non-canonical protein-protein interaction(s) responsible for significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 135 publications
(315 reference statements)
0
40
0
Order By: Relevance
“…Several reports suggested that PDIA3/ERp57 is associated with tumor progression and the modulation of STAT3 activity [60, 61]. Apurinic/apyrimidinic endonuclease/redox factor-1 (APE1/Ref-1) is a multifunctional protein that, in addition to its base excision DNA repair activity, exerts a redox control on cancer-associated transcription factors, including STAT3 [62]. Our studies, carried out on sixty-five FFPE tissues, confirmed the constitutively activation of STAT3 protein (pY 705 -STAT3) in tumor samples, without any relevant variation in expression levels between the Gleason grades.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggested that PDIA3/ERp57 is associated with tumor progression and the modulation of STAT3 activity [60, 61]. Apurinic/apyrimidinic endonuclease/redox factor-1 (APE1/Ref-1) is a multifunctional protein that, in addition to its base excision DNA repair activity, exerts a redox control on cancer-associated transcription factors, including STAT3 [62]. Our studies, carried out on sixty-five FFPE tissues, confirmed the constitutively activation of STAT3 protein (pY 705 -STAT3) in tumor samples, without any relevant variation in expression levels between the Gleason grades.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, oxidative stress DNA damage is known to induce APE1 for DNA repair thorough the BER pathway (Thakur et al 2015). APE1 itself favors as a redox co-activator of transcription factors the production of IL-6 Table 4 Univariate and multivariate logistic regression analysis of immunohistochemical expression differences in studied proteins between controls and cases after 34-week gestation…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we also focus our attention on the immunohistochemical expression of APE1/ Ref-1 (APE1). This is involved both in the base excision repair (BER) pathway of DNA lesions, acting as the major apurinic/apyrimidinic (AP) endonuclease, and in transcriptional regulation of gene expression, where it functions as a redox co-activator of different transcription factors that could lead to increased interleukin (IL)-6 and IL-8 expression (Cesaratto et al 2013;Thakur et al 2015;Tell et al 2005). IL-6 and IL-8 are two important immune-modulatory cytokines that are part of the senescence-associated secretory phenotype (SASP) (Coppé et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Redox factor-1 (Ref-1) is a multifunctional protein that contributes to both DNA repair and transcriptional regulation [2123]. Notably, Ref-1 is highly expressed in cancer cells and can have post-translational modifications, protein-protein interactions, redox activity, and roles in DNA repair, suggesting that it could be a useful therapeutic target gene [2123].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Ref-1 is highly expressed in cancer cells and can have post-translational modifications, protein-protein interactions, redox activity, and roles in DNA repair, suggesting that it could be a useful therapeutic target gene [2123]. Ref-1 increases gene expression by directly associating with transcription factors, including AP-1, EGR1, NF-κB, p53, STAT3, and HIF1α.…”
Section: Introductionmentioning
confidence: 99%